2002
DOI: 10.1042/0264-6021:3630581
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic degradation of plasma arginine using arginine deiminase inhibits nitric oxide production and protects mice from the lethal effects of tumour necrosis factor α and endotoxin

Abstract: Septic shock is mediated in part by nitric oxide (NO) and tumour necrosis factor alpha (TNFalpha). NO is synthesized primarily from extracellular arginine. We tested the ability of an arginine-degrading enzyme to inhibit NO production in mice and to protect mice from the hypotension and lethality that occur after the administration of TNFalpha or endotoxin. Treatment of BALB/c mice with arginine deiminase (ADI) formulated with succinimidyl succinimide polyethylene glycol of M(r) 20000 (ADI-SS PEG(20000)) elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
2
12
0
3
Order By: Relevance
“…A once-a-week injection of this enzyme in mice and humans is sufficient to eliminate all detectable arginine from the circulation (data not shown) and to block nitric oxide production. 12,27,28 This treatment is well tolerated in mice and preliminary results from human clinical testing indicate that this therapy is also well tolerated in humans. The initial clinical testing of this drug is limited to patients with melanoma and HCC because of the high incidence of ASS deficiency observed in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A once-a-week injection of this enzyme in mice and humans is sufficient to eliminate all detectable arginine from the circulation (data not shown) and to block nitric oxide production. 12,27,28 This treatment is well tolerated in mice and preliminary results from human clinical testing indicate that this therapy is also well tolerated in humans. The initial clinical testing of this drug is limited to patients with melanoma and HCC because of the high incidence of ASS deficiency observed in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at least three enzymes destroy arginine. The second enzyme is arginine decarboxylase (Philip et al, 2003), and the third is ADI, which we recently showed to have the ability to deplete plasma arginine and suppress LPS-induced NO production, suggesting a potential inhibitory role of ADI in NO-mediated angiogenesis (Noh et al, 2002;Thomas et al, 2002). Wilm et al (1996) purified a protein that strongly inhibited proliferation of vascular endothelial cells, later identified as ADI from Mycoplasma.…”
mentioning
confidence: 99%
“…Большинство клеток млекопитающих, вклю-чая гранулоциты, эритроциты, гепатоциты, ми-елоидные супрессорные клетки, тучные клет-ки, эндотелиальные клетки и гладкомышечные клетки, обладают в разной степени выраженной аргиназной и NOS активностью [101]. NOS мета-болизируют внутриклеточный аргинин с продук-цией цитрулина и оксида азота.…”
Section: метаболизм аргинина в эукариотических клет-кахunclassified
“…Данные об экспрессии ферментов, метаболизирующих аргинин, в моноцитах/ма-крофагах человека зачастую противоречат друг другу, что, вероятно, связано с разными методами выделения, разной тканевой принадлежностью, а также с разными способами культивирования и активации этих клеток. Значительно отлича-ются и методы детекции ферментов, а именно -в разных исследованиях изучается их экспрессия на уровне РНК, на уровне белка или же биоло-гическая активность [36,94,95,101]. Более того, в литературе высказываются сомнения относи-тельно важности этих ферментов как маркеров классической и альтернативной активации ма-крофагов человека [72].…”
Section: иммуносупрессорные эффекты аргининдеиминазыunclassified